Charakterystyka geotechniczna gruntów organicznych ze Szczecinka = The geotechnical characteristic of organic soils from Szczecinek - Wojnicka-Janowska, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Organie soils are characterized by disadvantageous geotechnical parameters are numbered to so called weak soils. Lake marl, gyttja and peat show great physically mechanical differentiation according to the kind and content of minerał and organical elements. In connection with great variability of examined soils, generalizations are possible only for selected areas of their occurrence. The present article shows the geotechnical characteristic of carbonale sediments originated from Szczecinek.
Keywords: grunty organiczne; charakterystyka geotechniczna; Szczecinek; organie soils; geotechnical characteristic